H2S Persulfidated and Increased Kinase Activity of MPK4 to Response Cold Stress in Arabidopsis - Du, Xinzhe; Jin, Zhuping; Liu, Zhiqiang; Liu, Danmei; Zhang, Liping; Ma, Xiaoli; Yang, Guangdong; Liu, Sha; Guo, Yarong; Pei, Yanxi (Frontiers in Molecular Biosciences, 2021)
Hydrogen sulfide (H2S) is a gasotransmitter along with nitric oxide and carbon oxide, which is involved in plant growth and development as well as biotic and abiotic stress resistance. In a previous study, we reported that mitogen-activated protein kinases, especially MPK4, are important downstream components of H2S involved in alleviating cold stress; however the underlying mechanism is unclear. In this study, we determined that the ability of H2S to alleviate cold stress is impaired in mpk4 mutants, but not in the upstream mek2 and crlk1 mutants. MPK4 was basically persulfidated, and NaHS (H2S donor) further increased the persulfidation level of MPK4. MEK2 was not persulfidated by H2S. NaHS treatments increased the MPK4 activity level nearly tenfold. The persulfidation signal of MPK4 did not disappear after 8 cystein residues in MPK4 were site-mutated, respectively. Above all, our results suggested that H2S alleviates cold stress directly by persulfidating MPK4 and increasing the MPK4 kinase activity.